2019
DOI: 10.1021/acssynbio.9b00078
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Genetically Encoded Biosensor for Detection of Polyketide Synthase Extender Units in Escherichia coli

Abstract: The scaffolds of polyketides are constructed via assembly of extender units based on malonyl-CoA and its derivatives that are substituted at the C2-position with diverse chemical functionality. Subsequently, a transcription factor-based biosensor for malonyl-CoA has proven to be a powerful tool for detecting malonyl-CoA, facilitating the dynamic regulation of malonyl-CoA biosynthesis, and guiding high-throughput engineering of malonyl-CoA dependent processes. Yet, a biosensor for the detection of malonyl-CoA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…129 Lastly, the physicochemical stability of DNA can be used to detect natural products such as biotin, vitamin D, and folate at nanomolar levels by strand displacement reactionbased biosensors, which have been shown to exhibit increased sensitivity, low interference, and high controllability. 130,131 The application of (small-molecule) biosensors and the development and engineering of new sensory devices is certainly of interest for different industries to meet performance criteria through the directed evolution of enzymes, 132,133 for the optimisation of microbial cell factories, [134][135][136] and the real-time monitoring of the production of target molecules 137 including (aromatic) alcohols, aldehydes, and acids, 112,113,[138][139][140][141] precursors for the synthesis fatty acids and their derivatives, 84,92,93,[142][143][144][145][146][147][148] isoprene and terpenoids, 149,150 steroids, as well as flavonoids. Biosensor systems for the last two will be highlighted in the following.…”
Section: Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…129 Lastly, the physicochemical stability of DNA can be used to detect natural products such as biotin, vitamin D, and folate at nanomolar levels by strand displacement reactionbased biosensors, which have been shown to exhibit increased sensitivity, low interference, and high controllability. 130,131 The application of (small-molecule) biosensors and the development and engineering of new sensory devices is certainly of interest for different industries to meet performance criteria through the directed evolution of enzymes, 132,133 for the optimisation of microbial cell factories, [134][135][136] and the real-time monitoring of the production of target molecules 137 including (aromatic) alcohols, aldehydes, and acids, 112,113,[138][139][140][141] precursors for the synthesis fatty acids and their derivatives, 84,92,93,[142][143][144][145][146][147][148] isoprene and terpenoids, 149,150 steroids, as well as flavonoids. Biosensor systems for the last two will be highlighted in the following.…”
Section: Biosensorsmentioning
confidence: 99%
“…Chromatographic analyses are time consuming but due to the complexity of the molecules, simple colorimetric or fluorometric assays are not typically applicable to PKS screening. 434 While biosensors for detecting enhanced precursor (e.g., malonyl-CoA) formation have been reported, 143,463 relatively few high-throughput methods for polyketide products are available. Kasey et al recently showed that engineered variants of the promiscuous erythromycinsensing transcription factor MphR could be used to detect related ligands like clarithromycin.…”
Section: Polyketidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging highthroughput strategies, including engineered transcription-factor biosensor platforms and colorimetric assays [24], offer promising tools for engineering polyketide biosynthesis. Recently, a newly refactored FapR-based biosensor system for the detection of a variety of C2-substituted CoA-and N-acetylcysteamine (SNAc)-linked extender units [73] was described, both in vivo and in vitro. This biosensor detected the over-production of mmCoA in an engineered E. coli strain and also detected other extender units, paving the way for high-throughput engineering of native and non-natural extender unit supply in producing organisms.…”
Section: High-throughput Approaches To Polyketide Synthetic Biologymentioning
confidence: 99%
“…A título de ilustração, uma busca na Web of Science em agosto de 2019 aponta para quase 86.000 artigos obtidos com o termo "biosensor". Há muitos artigos de revisão sobre biossensores (FABRI-FAJA et al, 2019;KALKREUTER et al, 2019;SU;LI;KERMAN, 2019) de maneira que não serão apresentadas informações detalhadas aqui. São discutidos apenas alguns aspectos introdutórios, com ênfase nos genossensores, que é o tipo de biossensor utilizado nesta tese.…”
Section: Capítulo 2-introdução E Revisão Bibliográficaunclassified